Faktor-Faktor yang Memengaruhi Partisipasi Tenaga Kerja dalam Program Kartu Prakerja : Institut Pertanian Bogor - Panjaitan, Dian Verawati; Nunung Nuryartono; Lukytawati Anggraeni (IPB University, 2021)
The initial objective of the Pre-Employment Card (Program KP) is to improve skills and prepare the workforce to be able to compete in the world of work. With the Covid-19 pandemic, the goal is to help people affected by the pandemic and reduce unemployment. After a year of implementing this program, it is necessary to conduct an analysis that aims to determine public sentiment towards the program and analyze the factors that influence a person's decision to register. Data from Drone Emprit Academic Open, Sakernas and the logit method were used to answer the objectives. The results show that the community gives negative sentiments related to the type of training and requirements. The factors that influence a person's decision to apply are the number of hours worked, income, age, training, job status, using the internet. Other factors are preparing for a new business, changes in income and working hours, and education level. The negative sentiment still arises in several issues related to the type of training and enrollment. PMO needs to improve how information is disseminated on requirements and registration. The training can be cheaper to allow more training attended and reach more recipients within the available budget.